A MULTILINGUAL THEMATIC PICTURE DICTIONARY FOR ASSISTING SIXTH GRADE ELEMENTARY SCHOOL STUDENTS’ LITERACY - Adnyani, Ni Komang Putri; Ratminingsih, N.M.; Budasi, I.G. (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Indonesia is known for having low literacy skills. Students' literacy skills are low because schools do not provide enough media to help students' literacy skills, especially dictionaries. This study aims to develop a multilingual thematic illustrated dictionary to assist sixth-grade elementary school students' literacy. This has an impact on student learning outcomes are low. In developing the dictionary, this study applies the Design and Development (D&D) using four instruments to collect data: observation sheets, interview guides, questionnaires, and expert assessments. The subjects of this study were teachers and students from elementary schools in urban and rural areas in Buleleng Regency, North Bali. The results show that this dictionary is relevant to the eleven criteria of a good multilingual thematic illustrated dictionary. This dictionary is also categorized as an excellent medium of 10 themes with words and sentences in three languages and authentic pictures. Thus, multilingual thematic illustrated dictionaries are a helpful medium for students and teachers to develop literacy skills. This research implies that students in learning can use the developed dictionary.